Anesthesia for trauma : new evidence and new challenges - Scher, Corey S. (Springer New York, 2014)
Anesthesia for Trauma is a comprehensive, clinically oriented text for practitioners and trainees in anesthesia, pain management, and critical care.  It covers core topics, from initial assessment and blood and blood products, to the multi-trauma patient and trauma by major anatomical region.  Burns receive especially extensive coverage.  Special considerations when administering anesthesia to traumatically injured children, pregnant women, and older people are reviewed, as are foundational areas such as clinically relevant physiology and the growing role of trauma simulation in training.  Readers will find leading edge coverage of microvascular surgery, pain management, and critical care of trauma patients as well as up-to-date chapters on trauma in the military, civilian trauma systems, and disaster management.  The book concludes with a unique "must-read" chapter for all clinicians on the link between substance abuse and penetrating trauma.